Far Lateral Approach - Luzzi, Sabino; Giotta Lucifero , Alice; Bruno, Nunzio; Baldoncini, Matias; Campero, Alvaro; Galzio, Renato (Acta Biomedica Atenei Parmensis, 2022)
The far lateral approach is an inferolateral extension of the lateral suboccipital approach. Designed for clipping of the aneurysms of the vertebrobasilar junction and proximal segments of the posterior inferior cerebellar artery, it became over the years a workhorse approach for ventral foramen magnum meningiomas and other intradural lesions located anterior to the dentate ligament.  This article summarizes the technical key aspects of the far lateral approach and transcondylar, supracondylar, and paracondylar extension.